Small Farm Food Safety, Fresh Produce: Part 5 - Your Farm Food Safety Plan - Brian Lapinski; Amy Simonne; Marilyn E. Swisher (EDIS)
FCS8846, a 3-page fact sheet by Brian Lapinski, Amy Simonne, and M.E. Swisher, is intended to help farmers come up with lists of best practices for food safety on their farms. Published by the UF Department of Family, Youth and Community Sciences, October 2007.